Mistisisme Makam Syekh Siti Jenar di Desa Lemahabang Kecamatan Doro Kabupaten Pekalongan - Medi Wasanjoyo (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2019)
Syekh Siti Jenar's tomb is present as a culture in the community. Through this tomb, people feel closer to God. The mysticism built by the community gave another view of the tomb. In his view, making rites an expression of something else or called mysticism and sacred. The main problem in this study is enough for two things; [1] How is Mysticism in Sheikh Siti Jenar's Tomb? [2] How is the Function of Sheikh Siti Jenar's Mysticism of the Manunggaling Kawulo Gusti for pilgrims? This study is a field research field research using qualitative descriptive methods, and uses a phenomenological approach, in this method intends to draw facts and phenomena that exist. The results of this study show that the surrounding community and pilgrims believe that Sheikh Siti Jenar's tomb has a negative aura that is mystical. So that Syekh Siti Jenar's grave is a form or form of community religiosity, especially for pilgrims who come to the tomb to ask for prayer and ask for peace of life through the remembrance of Syekh Siti Jenar's tomb, this action is manifested in the process of Manunggaling Kawulo Gusti. to his Lord, because the essence of God really exists in humans